THE ISSUE OF JUSTICE AND ASSISTANCE TO VICTIMS OF SEXUAL VIOLENCE IN SLOVAKIA (World Bulletin of Management and Law, 2023)
Sexual violence is recognized as a war crime in international law, but in reality few survivors ever see their attackers brought to justice. Weak rule of law, lack of legal recognition of the crime in many countries, lack of forensic evidence, lack of police response, and the risk of retaliation or stigma for survivors, all work together to prevent many from seeing the end of the long and winding road through the courts
Keywords: sexual violence; victims; survivors